A planar-sheet nongraphitic zero-bandgap sp 2 carbon phase made by the low-temperature reaction of γ-graphyne - Ali E. Aliev; Yongzhe Guo; Alexandre F. Fonseca; Joselito M. Razal; Zhong Wang; Douglas S. Galvão; Claire M. Bolding; Nathaniel E. Chapman-Wilson; Victor G. Desyatkin; Johannes E. Leisen; Luiz A. Ribeiro Junior; Guilherme B. Kanegae; et al. (Proceedings of the National Academy of Sciences, 2025)
The highest sheet symmetry form of graphyne, with one triple bond between each neighboring hexagon in graphene, irreversibly transforms exothermically at ambient pressure and low temperatures into a nongraphitic, planar-sheet, zero-bandgap phase consisting of intrasheet-bonded sp 2 carbons. The synthesis of this sp 2 carbon phase is demonstrated, and other carbon phases are described for possible future synthesis from graphyne without breaking graphyne bonds. While measurements and theory indicate that the reacting graphyne becomes nonplanar because of sheet wrinkling produced by dimensional mismatch between reacted and nonreacted sheet regions, sheet planarity is regained when the reaction is complete. Although the observed elimination of triple bonds to make parallel planar sp 2 carbon sheets likely requires ordered transformation within each sheet, diffraction data for reacted multisheet stacks indicate that the relative lateral positions of neighboring sheets are disordered, as predicted, since no crystalline diffraction peak (other than for the intersheet spacing) is observed.